Piezoelectric PVDF nanoparticles for enhanced antimicrobial activity via mechanical stimulation: A proof-of-concept study - Fernandes, Mariana Isabel Pires (2025)
The alarming rise of antimicrobial resistance is a public health issue, driven by the excessive and improper use of antibiotics, which are becoming less effective against an increasing number of microorganisms. There is an urgent need to find alternative antimicrobial strategies that can bypass bacterial resistance mechanisms. Using physical stimuli to sensitize bacteria to antimicrobial action is one step toward addressing this challenge. In this work, piezoelectric poly(vinylidene fluoride) (PVDF) nanoparticles were developed in an attempt to control and enhance the antimicrobial activity of materials through piezoelectric stimulation. The nanoparticles exhibited sizes ranging from 200 to 400 nm, with low polydispersity, a negative surface charge, and a spherical and smooth morphology. Using the reprecipitation methodology, the nanoparticles were synthesized through the crystallization of PVDF in the electroactive β-phase, achieving percentages of formulations greater than 80%. These nanoparticles demonstrated promising antimicrobial properties, which were considerably enhanced through dynamic conditions involving mechanical stimulation resulting in the creation of electroactive microenvironments. Notably, this dynamic approach exhibited a stronger inhibitory effect on bacterial growth, particularly against Escherichia coli. When water was used as nonsolvent for increasing the PVDF concentration to 10 mg/mL, it resulted in greater bacterial inhibition, with reductions of 1.33 log10 under static conditions and 2.21 log10 under dynamic conditions. However, this effect is less pronounced for Staphylococcus aureus. In contrast, when 50% ethanol solution is used as nonsolvent, both bacteria exhibited significant reductions: E. coli was completely eradicated under static conditions, while S. aureus showed a 1.93 log10 reduction. Under dynamic conditions, both bacteria were completely eliminated. Although these nanoparticles compromise the viability of human fibroblasts after 72 h of contact, this study provides a proof-of-concept for materials that enhance antimicrobial activity through mechanical stimulation. These findings open possibilities for developing hygienic coatings on public surfaces, leveraging pressure or touch to activate antibacterial effects.